Late morfofunctional alterations of the Sertoli cell caused by doxorubicin administered to prepubertal rats - Brilhante, Otavio; Okada, Fatima K.; Cerri, Estela Sasso [UNESP]; Stumpp, Taiza; Miraglia, Sandra M. (Biomed Central Ltd., 2012)
Background: Doxorubicin is a potent chemotherapeutic drug used against a variety of cancers. It acts through interaction with polymerases and topoisomerase II and free radical production. Doxorubicin activity is not specific to cancer cells and can also damage healthy cells, especially those undergoing rapid proliferation, such as spermatogonia. In previous studies our group showed that etoposide, another topoisomarese II poison, causes irreversible damage to Sertoli cells. Thus, the aim of this study was to address the effects of doxorubicin on Sertoli cell morphology and function and on the seminiferous epithelium cycle when administered to prepubertal rats.Methods: Prepubertal rats received the dose of 5 mg/Kg of doxorubicin, which was fractioned in two doses: 3 mg/Kg at 15dpp and 2 mg/Kg at 22dpp. The testes were collected at 40, 64 and 127dpp, fixed in Bouin's liquid and submitted to transferrin immunolabeling for Sertoli cell function analysis. Sertoli cell morphology and the frequency of the stages of the seminiferous epithelium cycle were analyzed in PAS + H-stained sections.Results: The rats treated with doxorubicin showed reduction of transferrin labeling in the seminiferous epithelium at 40 and 64dpp, suggesting that Sertoli cell function is altered in these rats. All doxorubicin-treated rats showed sloughing and morphological alterations of Sertoli cells. The frequency of the stages of the seminiferous epithelium cycle was also affected in all doxorubicin-treated rats.Conclusions and discussion: These data show that doxorubicin administration during prepuberty causes functional and morphological late damage to Sertoli cells; such damage is secondary to the germ cell primary injury and contributed to enhance the spermatogenic harm caused by this drug. However, additional studies are required to clarify if there is also a direct effect of doxorubicin on Sertoli cells producing a primary damage on these cells.
Keywords: Doxorubicin; Sertoli cell; Spermatogenesis; Rat; Transferrin